Role of endogenous testosterone concentration in pediatric stroke - Normann, Sandra; de Veber, Gabrielle; Fobker, Manfred; Langer, Claus; Kenet, Gili; Bernard, Timothy J.; Fiedler, Barbara; Sträter, Ronald; Goldenberg, Neil A.; Nowak-Göttl, Ulrike (Annals of neurology, 2009)
Previous studies have indicated a male predominance in pediatric stroke. To elucidate this gender disparity, total testosterone concentration was measured in children with arterial ischemic stroke (AIS; n = 72), children with cerebral sinovenous thrombosis (CSVT; n = 52), and 109 healthy controls. Testosterone levels above the 90th percentile for age and gender were documented in 10 children with AIS (13.9%) and 10 with CSVT (19.2%), totaling 16.7% of patients with cerebral thromboembolism overall, as compared with only 2 of 109 controls (1.8%; p = 0.002). In multivariate analysis with adjustment for total cholesterol level, hematocrit, and pubertal status, elevated testosterone was independently associated with increased disease risk (odds ratio [95% confidence interval]: overall = 3.98 [1.38–11.45]; AIS = 3.88 [1.13–13.35]; CSVT = 5.50 [1.65–18.32]). Further adjusted analyses revealed that, for each 1nmol/l increase in testosterone in boys, the odds of cerebral thromboembolism were increased 1.3‐fold. Ann Neurol 2009;66:754–758